2012
DOI: 10.1002/bsl.1996
|View full text |Cite
|
Sign up to set email alerts
|

The Inconsistency of Inconsistency Scales: A Comparison of Two Widely Used Measures

Abstract: This study compared the inconsistent responding validity scales of the Personality Assessment Inventory (PAI) and the Psychopathic Personality Inventory (PPI)/PPI-Revised (PPI-R) in two correctional samples to determine the extent to which they overlap in identifying invalid profiles. Results revealed substantial differences in the way the inconsistent responding validity scales of these measures performed. In particular, the PAI identified far fewer participants as having responded inconsistently compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Overall, we found that the IR scales are not effective for identifying careless responding in college samples, which is consistent with Nikolova et al's (2012) findings with correctional samples. Consequently, researchers and clinicians who use the PPI-R will not only have to rely on the DR scale to identify careless responders but will also be faced with the challenge of discerning whether high scores on the DR scale reflect careless reporting or overreporting.…”
Section: Limitations and Future Directionssupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, we found that the IR scales are not effective for identifying careless responding in college samples, which is consistent with Nikolova et al's (2012) findings with correctional samples. Consequently, researchers and clinicians who use the PPI-R will not only have to rely on the DR scale to identify careless responders but will also be faced with the challenge of discerning whether high scores on the DR scale reflect careless reporting or overreporting.…”
Section: Limitations and Future Directionssupporting
confidence: 91%
“…Note that the correlations between the PPI-R and corresponding TriPM scales were similar in magnitude for those below the cut on the DR or IR scales but that they appeared to be considerably higher for those above the cut on the IR scales than they were for those above the cut on the DR scale (Table 2). 3 The limited success of the IR scales in the current study lends support to Nikolova et al's (2012) concerns about the validity of IR scales and their call for additional research on the IR scales of other commonly used assessment instruments. IR scales may be capable of achieving adequate validity only if the item pairs that comprise the scale have challengingly high interitem correlations.…”
Section: Discussionmentioning
confidence: 70%
“…Re-running our logistic regression analyses using these cut scores (rather than dimensional scores) again resulted in a significant effect for the interaction term (Wald = 5.17, p < .05) on the second step (following FD and SCI on the first step), producing an odds ratio of 19.14. 7 Although the PPI-R contains an Inconsistency validity scale to detect random response profiles, Nikolova, Hendry, Douglas, Edens, and Lilienfeld (2012) raised concerns that this scale-which was developed in samples of community adults and undergraduates and has never been used in a psychiatric sample-might be prone to over-identify invalid profiles. Utilizing a cut score of 15 on the 15-item Inconsistency scale, 53 profiles (including 10 of the 19 participants who committed a predatory act) within our sample might be considered invalid.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent meta-analytic research (Ray et al, 2012) suggests that these concerns may be somewhat exaggerated due to the negligible or inverse correlations between positive impression management scales and psychopathic traits. Although the PPI-R does contain validity scales, research on their utility is in a nascent state at this time (e.g., Nikolova et al, 2012). Downloaded by [Florida International University] at 05:54 22 December 2014…”
Section: Discussionmentioning
confidence: 99%
“…The PPI has acceptable convergent validity with the PCL-R ( r = .43; Poythress et al, 2009) and test-retest reliability (r = .95; Lilienfeld & Andrews, 1996), and is sensitive to detecting inconsistent responding (Nikolova, Hendry, Douglass, Edens, & Lilienfeld, 2012). The PPI and PPI-R have two built-in validity scales (Deviant Responding and Variable Response Inconsistency) to detect deviant responding and inconsistent responding (Lilienfeld & Andrews, 1996) that have shown acceptable sensitivity and specificity in detecting invalid reports (Anderson, Sellbom, Wygant, & Edens, 2012).…”
Section: Introductionmentioning
confidence: 99%